Embracing Complexity: Preliminaries to a Posthumanist Approach to Non/Religious Diversity and Identities Beyond Binaries - Biano, Ilaria W. (Implicit religion, 2022)
The aim of the article is to propose a posthumanist approach to the issue of (non/religious) identity. Reflections at the intersection between post-humanism, study of religion, and identities help to better understand and clarify how core elements of posthumanism such as the decentring and relativization of the Human and the Anthropos do not mean that human beings don't matter at all, but they point out a specific, supposedly universal concept of Man. In this sense, central is an intersectional approach to identity and difference. While identity has always been constructed on dichotomies, Posthumanism, following previous forms of deconstruction, emphasizes the multiplicity of identities, their constructedness, and their constant multiple recombinations in innovative forms. An integrated posthumanist approach to the intersection of different aspects and components of identity, including non/religious ones, has the potential for highlighting both the idea that identity is not a monolithic concept, and the risks linked to a reification of something ultimately constructed - as it happens with identity politics, but also with its critics.